Pengawasan dalam Manajemen Pendidikan - Tadjudin, Tadjudin (Taallum: Jurnal Pendidikan Islam, 2013)
Among the functions of management, the function of control is very important. At this point, a manager should make an evaluation if the set up goal has been reached or not. If not yet, a manager should lead the people to make a reflection about the possible reasons for why the goal is not reached yet.